(untitled) (Universal International Scientific Journal, 2026)
This article explores the mechanisms for enhancing creativity in elementary school students through one of the most effective trends in education today - the STEAM approach. The article is not just about theory, but about the art of turning a child’s question "Why?" into an action question: "How can I create?"